Inhibition of protein N-myristoylation blocks Plasmodium falciparum intraerythrocytic development, egress and invasion - Anja C. Schlott (Public Library of Science (PLoS), 2021)
We have combined chemical biology and genetic modification approaches to investigate the importance of protein myristoylation in the human malaria parasite, Plasmodium falciparum. Parasite treatment during schizogony in the last 10 to 15 hours of the erythrocytic cycle with IMP-1002, an inhibitor of N-myristoyl transferase (NMT), led to a significant blockade in parasite egress from the infected erythrocyte. Two rhoptry proteins were mislocalized in the cell, suggesting that rhoptry function is disrupted. We identified 16 NMT substrates for which myristoylation was significantly reduced by NMT inhibitor (NMTi) treatment, and, of these, 6 proteins were substantially reduced in abundance. In a viability screen, we showed that for 4 of these proteins replacement of the N-terminal glycine with alanine to prevent myristoylation had a substantial effect on parasite fitness. In detailed studies of one NMT substrate, glideosome-associated protein 45 (GAP45), loss of myristoylation had no impact on protein location or glideosome assembly, in contrast to the disruption caused by GAP45 gene deletion, but GAP45 myristoylation was essential for erythrocyte invasion. Therefore, there are at least 3 mechanisms by which inhibition of NMT can disrupt parasite development and growth: early in parasite development, leading to the inhibition of schizogony and formation of “pseudoschizonts,” which has been described previously; at the end of schizogony, with disruption of rhoptry formation, merozoite development and egress from the infected erythrocyte; and at invasion, when impairment of motor complex function prevents invasion of new erythrocytes. These results underline the importance of P. falciparum NMT as a drug target because of the pleiotropic effect of its inhibition. Understanding the essential factors needed for malaria parasite development could help us find new therapeutic targets. This study reveals that N-myristoylation is a posttranslational modification of proteins essential for the parasites’ growth and their invasion of red blood cells.